Ultrasonic study of molecular interactions in binary mixtures of methyl methacrylate(MMA) with toluene and dimethylacetamide at 318 K - Indhumathi, R.G. (International Journal of Advanced Chemistry, 2016)
The ultrasonic velocity, density and viscosity at 318K have been measured in the binary systems of Methyl methacrylate + Toluene and Methyl methacrylate + Dimethylacetamide. In this work an attempt has been made for the first time to investigate the behavior of binary solutions of Methylmethacrylate(MMA) in Toluene and Dimethylacetamide(DMAC) with regard to acoustical parameters such as adiabatic compressibility(β), intermolecular free length(lf), free volume(Vf), Rao’s constant(R), Wada’s constant(W) and specific acoustical impedance(Z) from ultrasonic measurements at 318 K were calculated. The results are interpreted in terms of molecular interaction between the components of mixtures.